Johannes die Doper in Betanië oorkant die Jordaan - Nortjé-Meyer, Lilly (Hervormde teologiese studies, 1989)
John the Baptist in Bethany across the Jordan There a re two places in the Fourth Gospel called ‘Bethany’. One is the well-known site near Jerusalem. The other is the lesser-known locality where John the Baptist started his career as the ‘Baptist’. This paper traces John’s use of ‘Bethany across the Jordan’. It is contended th a t the site has more than geographical significance. In analysis the theological purpose of the site is demonstrated. It is the spot where the two Johannine worlds meet: The world above and the world below. This Johannine dualism is resolved a t one spesific time and place, viz at this Bethany. The locality therefore has the theological significance as point of departure for the narration of the coming of Gods only begotten son, who is the Lamb of God, who takes away the sin of the world.